Skene Duct Cyst in Childhood: A Case Report - Agung Wijaya Kusuma; Bobby Indra Utama; Yulia Margaretta Sari (Universitas Andalas, 2023)
Introduction. Vaginal cysts are uncommon and may be either congenital or acquired. the most common vaginal cysts is a urothelial cyst or a paraurethral cyst. With an incidence of 1 in every 2000–7000 live births, paraurethral cysts are an uncommon cause of interlabial mass in newborns and account for less than 0.5 per cent of all congenital urinary system anomalies. Study Purpose. This report describes a rare Vaginal cyst in a child at the posterior vaginal wall.. Results.this is a case report study about a girl 1-year-8-months old with vaginal cyst since the age of 2 months. Physical examination and ultrasound finding revealed a cystic mass size 3x3x1 cm in posterolateral of the right vaginal wall extended to right periurethral. Management of this case was extirpation of the vaginal cyst.Conclusion. A vaginal cyst is an uncommon case in a child. Vaginal cysts have several possible etiologies, such as possibly embryological origin, ectopic inclusion tissue or possibly due to urological abnormalities. Diagnosis requires a thorough understanding of diagnostic possibilities and a systematic evaluation. This patient has been treated with surgical excision due to a high success rate.